Significant Association between Microrna Gene Polymorphisms and Type 2 Diabetes Mellitus Susceptibility in Asian Population: A Meta-Analysis - Zhifang DENG; Wenqi GAO; Wei LUO; Li AI; Min HU (Tehran University of Medical Sciences, 2020)
Background: The gene polymorphisms in microRNA might relate to susceptibility of type 2 diabetes mellitus (T2DM). However, the results of existing studies were inconsistent and obscure. To investigate the precise associations between microRNA gene polymorphisms and T2DM risk, the present meta-analysis was performed. Methods: The literatures were searched from four electronic databases, PubMed, Embase, CNKI and Wanfang. Subsequently, odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were both used to evaluate the associations between two single nucleotide polymorphisms (SNPs) (microRNA146a rs2910164 (G>C), microRNA124a rs531564 (C>G)) and risk of T2DM in Asian population. Results: Totally, there were 4 studies included in our present analysis in the language of English and Chinese. There were partly significant associations between susceptibility of T2DM and SNPs (microRNA146a rs2910164 (G>C), microRNA124a rs531564 (C>G)). The G allele in microRNA146a rs2910164 (G>C) and C allele in microRNA124a rs531564 (C>G) both presented remarkably reduced risk of T2DM when compared with the healthy population. Conclusion: The microRNA146a rs2910164 (G allele) and microRNA124a rs531564 (C allele) might function as protective factors in the pathogenetic process of T2DM in Asian population.